If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(y-1)+y=14
We move all terms to the left:
2(y-1)+y-(14)=0
We add all the numbers together, and all the variables
y+2(y-1)-14=0
We multiply parentheses
y+2y-2-14=0
We add all the numbers together, and all the variables
3y-16=0
We move all terms containing y to the left, all other terms to the right
3y=16
y=16/3
y=5+1/3
| x+(1+4x)=106 | | Y/3+y=8 | | -16(d+1)=-20 | | x10+3x5=72 | | 9-3x-1=5x+2 | | 8x-17=4x+33 | | 3x-3=6-(9x-9) | | 14s+20=-13+10s-15 | | -13=3+2k | | -25+x=5(8x-5) | | 2x–1=1–2x | | -8n=-80 | | 77+11y=77 | | 4x+5=195 | | 3j+14=4j | | 34(2m+1)=2 | | 6=84/c | | (5x+10)/(x+2)=0 | | 30=1x | | -2.3u=-0.9u+12.04 | | 25(w-2)=-2 | | -1(2x+5)+14=22 | | 1-x=-11-5x | | 2x=3=15 | | -11m=-16-7m | | -2+25x-+17=-35 | | (7x-1)=9x+5 | | 12n+10n+19=-15+20n | | b+23=14b-1 | | 9c+-1=10 | | -89=1-3(2-4x) | | -32-8r=16 |